Artificial intelligence - Boden, Margaret A. (Handbook of perception and cognition (2nd ed.), 1996)
Artificial Intelligence is the study of how to build or program computers to enable them to do what minds can do. This volume discusses the ways in which computational ideas and computer modeling can aid our understanding of human and animal minds. Major theoretical approaches are outlined, as well as some promising recent developments. Fundamental philosophical questions are discussed along with topics such as: the differences between symbolic and connectionist AI, planning and problem solving, knowledge representation, learning, expert systems, vision, natural language, creativity, and human-computer interaction. This volume is suitable for any psychologist, philosopher, or computer scientist wanting to know the current state of the art in this area of cognitive science. Key Features * Up-to-date account of how computational ideas and techniques are relevant to psychology * Includes discussions of "classical" (symbolic) AI, of connectionism (neural nets), of evolutionary programming, and of A-Life * Discusses a wide range of psychology from low-level vision to creativity